2022
DOI: 10.1042/cs20220011
|View full text |Cite
|
Sign up to set email alerts
|

A time to heal: microRNA and circadian dynamics in cutaneous wound repair

Abstract: Many biological systems have evolved circadian rhythms based on the daily cycles of daylight and darkness on Earth. Such rhythms are synchronised or entrained to 24-h cycles, predominantly by light, and disruption of the normal circadian rhythms has been linked to elevation of multiple health risks. The skin serves as a protective barrier to prevent microbial infection and maintain homoeostasis of the underlying tissue and the whole organism. However, in chronic non-healing wounds such as diabetic foot ulcers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 182 publications
0
4
0
Order By: Relevance
“…A detailed review of the function of all these cell type–specific clocks is beyond the scope of this paper; the reader is instead referred to relatively recent published literature. 23 , 44 , 47 , 48 , 49 Here, we provide detail regarding how cell- and animal-based studies, in combination with state-of-the-art hypothesis-testing and hypothesis-generating strategies, have yielded considerable insight into the physiologic role of the cardiomyocyte circadian clock.…”
Section: Cell-autonomous Circadian Clocksmentioning
confidence: 99%
“…A detailed review of the function of all these cell type–specific clocks is beyond the scope of this paper; the reader is instead referred to relatively recent published literature. 23 , 44 , 47 , 48 , 49 Here, we provide detail regarding how cell- and animal-based studies, in combination with state-of-the-art hypothesis-testing and hypothesis-generating strategies, have yielded considerable insight into the physiologic role of the cardiomyocyte circadian clock.…”
Section: Cell-autonomous Circadian Clocksmentioning
confidence: 99%
“…Previous studies showed a sleep-wake cycle-dependent hematopoietic release of granulocytes and monocytes and subsequent traffic of these cells to various tissues (110,(354)(355)(356). Although rhythmic leukocyte homing to skin seems to be neglectable in the steady state (355), indirect evidence indicates that there is a circadian regulation of immune cell traffic to the skin upon wounding and upon microbial or antigenic challenges (357)(358)(359)(360)(361)(362). Likewise, tissue-resident innate immune cells like dendritic cells (363,364), mast cells (317,365,366) or macrophages (367)(368)(369) show circadian regulation that impacts cutaneous responses to antigens and allergens, respectively.…”
Section: Potential Effects Of Shift Work On Innate Immune Cells In Th...mentioning
confidence: 99%
“…A potential ECM modulator is the circadian clock. Regulation of the ECM components by circadian clock genes and related processes have been demonstrated in various tissues including the nervous, squamous epithelium, connective/cartilage, liver, kidney, and cardiac muscle [41][42][43][44][45][46][47][48][49][50]. Circadian regulation of the ECM has been minimally studied in the lung, but analyzing similar processes and structures in different tissues could be a starting point for future investigations.…”
Section: Circadian Modulation Of the Ecm Throughout The Bodymentioning
confidence: 99%
“…Furthermore, recent findings suggest that EVs and the protein cargo they carry may be circadian-regulated [51,52]. In the squamous epithelium, recent evidence suggests that microRNAs function as intercellular communicators for wound repair processes through transportation via extracellular vesicles [43]. Although various tissues throughout the body differ functionally, many molecular and intercellular processes are maintained universally.…”
Section: Circadian Modulation Of the Ecm Throughout The Bodymentioning
confidence: 99%